The Complexities of Canine Monocytic Ehrlichiosis: Insights into Ehrlichia canis and Its Vector Rhipicephalus sanguineus - Joana Ferrolho; Sandra Antunes; Hugo Vilhena; Sofia Anastácio; Sérgio Ramalho de Sousa; Gonçalo Frouco; Bárbara Ferreira; Ana Domingos (Microbiology Research)
Canine monocytic ehrlichiosis (CME) is a highly infectious disease with zoonotic potential. Ehrlichia canis, the causative agent, is primarily transmitted by Rhipicephalus sanguineus. Tick infestation and tick-borne diseases (TBDs) are serious human and veterinary health problems due to the lack of efficient control measures. This review aims to provide information about CME, detailing epidemiology, pathogenesis, clinical manifestations, and current strategies for diagnosis, treatment, and prevention. The review delves into the biology of R. sanguineus, exploring its lifecycle, habitat, and mechanisms of E. canis transmission. Ehrlichia canis infection follows a three-phase transition: acute, subclinical, and chronic, with distinct clinical signs, from mild to severe and even life-threatening in some cases, with the potential for asymptomatic long-term carriers acting as reservoirs. Pathogenesis involves complex interactions between the pathogen and host immune responses, influencing disease severity and progression. Additionally, the review highlights challenges in controlling CME due to the widespread distribution of R. sanguineus. Genetic diversity within R. sanguineus populations and their varying vector competence further complicate control efforts. The role of environmental changes in tick distribution aligns the control of CME within the One Health concept, integrating approaches to improve outcomes for humans, animals, and the environment. Preventive measures on tick control and potential vaccine development are also reviewed.